O espetáculo da palavra televisionada: a entrevista como imagem de si nas eleições presidenciais de 2018 - Possa, Júlia Maziero (2019)
This research concerned by the study of the self images constructed by Jornal Nacional and Rede Globo from the questions and interventions made during the interviews with the presidential candidates during the first round of the 2018 electoral period. The objective is to analyze the images of himself constructed by Rede Globo through journalists of Jornal Nacional stand during an interview with the then presidential candidate, Jair Bolsonaro, on August 28, 2018, a date marked by the Brazilian electoral period. The central theoretical framework is given by the Semiolinguistic Theory established by Charaudeau (2005, 2016a, 2018a) and Bourdieu's Theory of Symbolic Exchanges (1989, 1996). The work is justified by the emergence in realizing the effects of media and language in use in society, especially during a sharp political crisis. In addition, it is also justified by the opportunity to intersect the areas of Linguistics and Social Communication, reaffirming the role of language as a formative agent of society. The corpus of analysis of this research is composed by the interview conducted by Rede Globo's Jornal Nacional, with the candidate Jair Bolsonaro on August 28, 2018 - a choice that is due to the repercussion of the interview and subsequent election of the then candidate. In methodological terms, this work has a qualitative approach and is characterized as descriptive-exploratory and case study. The construction of self images, given by EUc-Rede Globo through EUe-Journalists, linked to disbelief to power and politics in general is one of the results obtained. In addition, we verified that the staging given by the broadcaster is always directed to the spectator public (TUd-Telespectador), considering strategies of influence and delegitimation of the candidate's speech. The full picture taken from the interview reveals that EUc-Rede Globo built an image of itself that sought to situate the broadcaster in the 'counterpower'. One of the possible interpretations is that such a movement could garner 'truth' from it and therefore its own 'legitimacy'.